Adjective position in the code-switched speech of Spanish and Papiamento heritage speakers in the Netherlands: Individual differences and methodological considerations - van Osch, Brechje; Parafita Couto, M. Carmen; Boers, Ivo; Sterken, Bo (Frontiers in Psychology, 2023)
Introduction This study examines adjective-noun order in code-switched constructions by heritage speakers of Spanish and Papiamento in the Netherlands. Given that Dutch differs from Spanish and Papiamento regarding the default position of the adjective, word order in the nominal domain creates a so-called “conflict site” in code-switching. Most accounts of word order patterns in code-switching focus on structural constraints, such as the matrix language or the strength of the EPP feature in Agr. Thus far, studies comparing the two models have not found compelling evidence for either of them. Methods The present study takes a more comprehensive approach and considers several linguistic (matrix language, adjective language, and type of insertion) as well as extra-linguistic variables (e.g., age, age of onset, and patterns of exposure and use). Moreover, we compare heritage speakers of two different heritage languages that are linguistically similar (both Spanish and Papiamento exhibit postnominal adjectives), and share the same dominant societal language, but are likely to differ from each other in terms of certain sociolinguistic properties. 21 Spanish and 15 Papiamento heritage speakers (aged 7–54) in the Netherlands carried out a Director-Matcher task, aimed at eliciting nominal constructions containing switches. Results The results show that either the ML or the language of the adjective, or both, are important predictors for word order, although the data cannot disentangle these two factors. Moreover, the type of insertion was found to play a role: word order patterns for noun insertions differed from other types of insertions. In addition, the two groups did not behave similarly: Papiamento speakers were more categorical in their preference for noun-adjective order when inserting Dutch nouns into their heritage language than the Spanish speakers were. Finally, there was a great deal of individual variation, which seemed to be related mostly to the age of the participants: children and teen participants behaved differently from adults. Discussion These findings demonstrate that both linguistic and extra-linguistic play a role in determining how heritage speakers deal with conflict sites in the nominal domain. Particularly, the findings suggest that, at least for some communities and in some code-switching modes, children may need more time, or more input, too converge on adult-like code-switching norms.